Chemical constituents of Piptadenia gonoacantha (Mart.) J.F. Macbr (pau jacaré) - Carvalho,Mário G. de (2010)
The phytochemical investigation of Piptadenia gonoacantha (Mart.) J.F. Macbr. (Leguminosae-Mimosoideae), commonly known as "pau jacaré" (alligator stick), afforded sitosterol, campesterol, stigmasterol, the N-benzoylphenylalanine-2-benzoylamide-3-phenylpropyl ester, known as asperphenamate, sitosterol-3-O-β-D-glucopyranoside, besides three flavonoids, apigenin, 5-O-methylapigenin and 7,4'-dihydroxy-3',5-dimethoxyflavone from its branches. From its leaves, the methyl gallate and two flavonoids, vitexin and isovitexin, were isolated. From its bark, a mixture of sitosterol, campesterol, and stigmasterol, besides a mixture of cycloartenone, cycloartan-25-en-3-one, and 24-methylene-cycloartenone, and the pure triterpenes 24-methylenecycloartanol, friedelin, lupeol and lupenone, were isolated. Their structures were established on the basis of spectral analysis, comparison with literature data and GC-MS analysis of the mixtures. The ester, flavonoids and the cycloartanes are been identified for first time in the genus Piptadenia.